Enterprise Resource Planning Implementation: User Satisfaction on Service Information System Quality - I Made Yuko Dharma Putra; Dewi Nusraningrum (Universitas Mercu Buana, 2022)
Objectives: This study was conducted to analyze the success of ERP implementation and user satisfaction after using the ERP system at flexible packaging manufacturing companies.Methodology: This study uses a quantitative method with causal analysis using tools from Smart PLS. The population of this study are ERP system users with a sample of 300 respondents using a random sampling technique The population of this study includes all employees of flexible packaging manufacturing companies. The respondents in this study are employees who use ERP systems.Finding: The results found that the greater the quality of the system provided, the better will the user satisfaction Increased user satisfaction can be achieved by producing good quality information, and good service quality of a system will also increase user satisfaction. Satisfied users will increase the benefits received by the company in its business processes.Conclusion: Greater benefits can be received by improving information quality, service quality, and system quality, and. User satisfaction can be used as a mediation of information quality, service quality, and system quality towards the successful implementation of ERP.